PENGARUH KOMPETENSI, KOMITMEN ORGANISASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA MELALUI PRODUKTIVITAS KERJA KARYAWAN MANHATTAN HOTEL JAKARTA - Meylani Tuti; Agus Riyanto; Nanda Maulina (LPPM Universitas Asa Indonesia, 2020)
The purpose of this study is to determine the influence of Competency, organizational commitment and career development on performance through variable work productivity. The sample involved was 200 respondent of employees Manhattan Hotel with a nonprobability sampling method. The data of this study were obtained from distributing questionnaire. Method of analysis is Path analysis, follow by transforming data using Method of Successive Interval(MSI), Malahanobis distance test, normality test, multicollinearity test, linearity test, heteroscedasticity test, correlation analysis, and mediation testing with sobel test. The results of this study are competency, organizational commitment, career development, work productivity and performance employee have a positive directly effect. Then organizational commitment and career development have an indirect positive impact to the performance through work productivity. Beside that, competency no indirectly effect on employee performance through work productivity as a mediating variable.